TREND OF PROFESSIONAL IDENTITY OF GUIDANCE AND COUNSELING TEACHERS - Ibrahim Al Hakim (Universitas Pendidikan Indonesia, 2023)
Teacher is a profession so it has a professional identity. The professional identity of the teacher supports him as a professional. The point is that a person will work professionally if he has high work skills and a sincere heart to do his best. The ability of guidance and counseling teachers (guidance and counseling teachers) or counselors to live a professional identity as part of themselves ideally becomes a necessity. The purpose of this study is to determine the tendency of professional identity based on the theoretical dimensions of counseling teachers in Banten Province. This research method used is a quantitative survey method of 252 guidance and counseling teacher, 55 (22%) male participants and 197 (78%) female participants. All participants came from eight regencies/cities in Banten Province. Based on the research results, it was found that there were 31 participants (12%) who were in the diffuse identity category, 185 participants (73%) were in the moratorium category, and 36 participants (14%) were in the achievement mature identity category. The general results of the analysis of the tendency for professional identity of counseling teachers show that counseling teachers are dominantly in the moratorium category, which means that counseling teachers tend to have the motivation to continue exploring their profession but do not yet have a strong commitment.